UV-induced selective oxidation of Met5 to Met-sulfoxide leads to the formation of neurotoxic fibril-incompetent α-synuclein oligomers. (September 2014) - Carmo-Gonçalves, Phelippe; Pinheiro, Anderson S.; Romão, Luciana; Cortines, Juliana; Follmer, Cristian
Abstract Oxidative stress and the formation of cytotoxic aggregates of the presynaptic protein α-synuclein (AS) are two important events associated with the pathogenesis of Parkinson's disease (PD) and several other neurodegenerative diseases. In this context, extensive efforts have been made to elucidate the molecular basis of the cytotoxic synergy between oxidative stress and AS aggregation. In this study, we demonstrate that the exposure of AS to oxidative stress induced by UV radiation (ASUV) blocks the protein fibrillation, leading to the formation of highly toxic fibril-incompetent oligomers. In addition, ASUV exhibited stronger anti-fibrillogenic properties than H2O2-treated AS, inhibiting the fibrillation of unmodified AS at notably low concentrations. Mass spectrometry indicated that Met5 oxidation to Met-sulfoxide was the only modification promoted by UV exposure, which is reinforced by NMR data indicating that Met5 is the only residue whose amide resonance completely disappeared from the 1H-15N HSQC spectrum after UV exposure. This result is supported by previous data that indicate that C-terminal Met residues (Met116 and Met127) and N-terminal Met1 are less susceptible to oxidation than Met5 because of the residual structure of the disordered AS monomer. Overall, our findings suggest that specific oxidation of Met5 might be sufficient to promote the formation of highly neurotoxic oligomers of AS.